Peasant territorialities in Loja, Ecuador: analysis of its organizational dynamics from three cases - Alvarado Torres, Marco Antonio (2018)
In the province of Loja, located south of Ecuador, since the 90s of the last century, several peasant families have created local organizations through which promote alternative territorialities, how ecological production, solidarity finance, community management of water, defense of ancestral lands, empowerment of rural women, amongst other activities. This paper asks how these experiences are structured, and from participatory elaboration of sociograms, analyzes the internal dynamics of three organizations, and its interactions with other actors. These territorialities are more than simple practices of production, or management, these are also complex phats of political subjectivation.